PENGARUH LEVERAGE, FIRM SIZE, INSTITUTIONAL OWNERSHIP, DAN TRANSFER PRICING TERHADAP TAX AVOIDANCE (PENGHINDARAN PAJAK) (Studi pada Perusahaan Infrastruktur, Utilitas, dan Transportasi yang Terdaftar di BEI secara berturut-turut Tahun 2017-2021 - Farah Ordina Ardha Sukma; Erma Setiawati (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The company is one of the parties that contributes to tax revenues. Tax is considered a significant burden for the company, because it reduces the company's income. This encourages companies to practice taxavoidance. This study aims to analyze the effect of leverage, firm size, institutional ownership, and transfer pricing on tax avoidance. The population in this study are infrastructure, utilities and transportation companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The research sample was determined by purposive sampling in order to obtain 21 companies as a sample. This study uses data analysis techniques multiple linear regression. The results in this study are leverage, institutional ownership, and transfer pricing have no effect on tax avoidance. Meanwhile, firm size has an effect on tax avoidance.